2017
DOI: 10.1007/s10815-017-1030-3
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin levels, but not Hp1-Hp2 polymorphism, are associated with polycystic ovary syndrome

Abstract: Hp1-Hp2 polymorphism is not associated with PCOS but plasma Hp could be a potential biomarker for PCOS and its complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
13
0
3
Order By: Relevance
“…Proteomic studies have suggested that haptoglobin -an inflammatory acute phase glycoprotein -may be also associated to PCOS (Matharoo-Ball et al 2007;Insenser et al 2010). More recently, we conducted a case-control study (Carvalho et al 2017b) that showed higher plasma haptoglobin levels in the PCOS group than in controls. In the aforementioned study, haptoglobin also showed a positive correlation with C-reactive protein (CRP) and pro-oxidative profile in the PCOS group.…”
Section: Pathophysiology Of Pcosmentioning
confidence: 86%
See 1 more Smart Citation
“…Proteomic studies have suggested that haptoglobin -an inflammatory acute phase glycoprotein -may be also associated to PCOS (Matharoo-Ball et al 2007;Insenser et al 2010). More recently, we conducted a case-control study (Carvalho et al 2017b) that showed higher plasma haptoglobin levels in the PCOS group than in controls. In the aforementioned study, haptoglobin also showed a positive correlation with C-reactive protein (CRP) and pro-oxidative profile in the PCOS group.…”
Section: Pathophysiology Of Pcosmentioning
confidence: 86%
“…There is an imbalance in PCOS between pro-inflammatory mediators and anti-inflammatory cytokines, which is associated with a systemic low-grade inflammation in these women (Duleba and Dokras 2012;Mortada et al 2015;Soter et al 2015;Aytan et al 2016). Inflammation is considered to be a strong link between the numerous metabolic ramifications of the syndrome, such as IR, dyslipidemia, and T2DM (Repaci et al 2011), and may also contribute to an increased risk of cardiovascular complications in PCOS (Repaci et al 2011;Soter et al 2015;Carvalho et al 2017b).…”
Section: Pathophysiology Of Pcosmentioning
confidence: 99%
“…Dyslipidemia is the most common metabolic disorder in PCOS patients [42]. It has a prevalence rate of 70% and is positively correlated with IR [43]. IR reduces ability of the insulin to inhibit lipase, leading to a high level of free fatty acids and an increase in the risk of obesity and cardiovascular diseases in PCOS patients.…”
Section: Ir and The Metabolic Abnormality In Women With Pcosmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of studies on Brazilian populations. Seven studies were from the Northeast region [23][24][25][26][27][28][29], thirteen studies were from the Southeast [30][31][32][33][34][35][36][37][38][39][40][41][42], five studies were from the South [43][44][45][46][47], and two studies were from the Midwest region [48,49]. No data from the North region were available.…”
Section: Discussionmentioning
confidence: 99%